Effect of Freeze-Thaw Cycles on the Internal Structure and Performance of Semirigid Base Materials - Yiqi Wang; Yiqiu Tan; Meng Guo; Xinglong Wang (Advances in Materials Science and Engineering)
In this study, we investigate the spatial distributions of the internal structures in semirigid base materials (SRBMs) and explore their effect on the service performance of the SRBMs. X-ray computed tomography (X-ray CT) was used to conduct a spatial voids structure analysis. Three variates were selected to study the factors influencing the spatial distributions of the internal structures, including freeze-thaw cycles, curing time, and cement content. The results show that, with the increase in the number of freezing and thawing cycles, the average porosity, void area, and void number of the SRBM samples increased, and the average void diameters of all samples initially increased and then decreased. These trends led to an increase in the mass loss ratio and strength loss ratio. Increasing the cement content and extending the curing time decreased the average number of voids, average void area, and average void diameter and decreased the mass loss ratio and strength loss ratio of the SRBMs. The top and bottom of the SRBM samples were more porous than the middle of the samples, whereas the maximum value of the average void diameter was observed in the middle of the samples.